Comparison between phonetic system of Mandarin and Malay language / Ting Hie-Ling - Ting, Hie-Ling (Akademi Pengajian Bahasa, 2021)
Mandarin and Malay language show a quite number of differences in its phonetic attributes and the consequent Malay learners encountered difficulties in learning Mandarin phonetic system especially at the beginner level of learning Mandarin. Inaccurate or mistake in pronunciation could contribute to misunderstanding in a conversation. Hence, it is deemed to carry out a comparative study on the phonetic and phonology between Mandarin and Malay language as it is a tool to helps learners to understand the basic notion of pronunciation in a language. Comparing the manner of articulation and the place of articulation is the best way to demonstrate the phonological diversity in a language. For that reason, this current study employed a comparative description of qualitative method to describe the similarities and differences between phonetic of Mandarin and Malay language. Findings indicate that: (i) Mandarin and Malay language share two similar cardinal vowels and eight similar consonants; (ii) there are one cardinal vowels and five consonants does not exist in both languages; (iii) Mandarin have 39 compound vowels while Malay language have only 3 compound vowels which known as diphthongs; (iv) both languages have 15 consonants that are similar in their alphabet writing system but not identical in term of manner and place of articulation